Variation in general practice prostate‐specific antigen testing and prostate cancer outcomes: An ecological study. Issue 2 (12th June 2014) - Hjertholm, Peter; Fenger‐Grøn, Morten; Vestergaard, Mogens; Christensen, Morten B.; Borre, Michael; Møller, Henrik; Vedsted, Peter
<x xml:space="preserve">Abstract</x> Knowledge is sparse about the consequences of variation in prostate‐specific antigen (PSA) testing rates in general practice. This study investigated associations between PSA testing and prostate cancer‐ related outcomes in Danish general practice, where screening for prostate cancer is not recommended. National registers were used to divide general practices into four groups based on their adjusted PSA test rate 2004–2009. We analysed associations between PSA test rate and prostate cancer‐related outcomes using Poisson regression adjusted for potential confounders. We included 368 general practices, 303, 098 men and 4, 199 incident prostate cancers. Men in the highest testing quartile of practices compared to men in the lowest quartile had increased risk of trans‐rectal ultrasound (incidence rate ratio (IRR): 1.20, 95% CI, 0.95–1.51), biopsy (IRR: 1.76, 95% CI, 1.54–2.02), and getting a prostate cancer diagnosis (IRR: 1.37, 95% CI, 1.23–1.52). More were diagnosed with local stage disease (IRR: 1.61, 95% CI, 1.37–1.89) with no differences regarding regional or distant stage. The IRR for prostatectomy was 2.25 (95% CI, 1.72–2.94) and 1.28 (95% CI, 1.02–1.62) for radiotherapy. No differences in prostate cancer or overall mortality were found between the groups. These results show that the highest PSA testing general practices may not reduce prostate cancer mortality but increase the downstream use of diagnostic and surgical procedures with potentially harmful side effects.